Fungal diversity and metabolomic profiles in GM and isogenic non-GM maize cultivars from Brazil - Gasperini, A. M.; García-Cela, Esther; Sulyok, Michael; Medina, Angel; Magan, Naresh (Springer, 2020)
There is little knowledge of the microbial diversity, mycotoxins and associated secondary metabolites in GM maize and isogenic non-GM cultivars (cvs). This study has quantified the microbial populations and dominant fungal genera in 6 cvs of each type representative of herbicide, pesticide or stacked resistance to both. The predominant mycotoxins and targeted metabolomics profiles were also compared between the two sets of cvs. This showed that the overall fungal populations were 8.8 CFUs g−1 maize. The dominant genera, isolated from maize samples, whether surface-sterilised or not, in all maize cvs were Fusarium, followed by Penicillium, Aspergillus and occasionally Cladosporium and Alternaria. The analysis of the targeted metabolomics showed that approx. 29 different metabolites were detected. These were dominated by fumonisins and minor Penicillium spp. metabolites (questiomycin A and rugulovasine A). Interestingly, the range and number of mycotoxins present in the GM cvs were significantly lower than in the non-GM maize samples. This suggests that while the fungal diversity of the two types of maize appeared to be very similar, the major contaminant mycotoxins and range of toxic secondary metabolites were much lower in the GM cvs.
Keywords: Fungal diversity; Mycotoxigenic fungi; Metabolomics; Toxic secondary metabolites; Selective media; Maize cultivars; GM; non-GM